THE IMPACT OF COVID-19 ON GLOBAL SHIPPING AND MARITIMEINDUSTRY IN INDONESIAN AND HOW TO COPE WITH THE CORONAVIRUS OUTBREAK BASED ON RECOMMENDATIONS WHO AND IMO - Muhammad Nur Candra; Supriyanto Supriyanto; Teguh Herlambang (Indonesian Naval Technology College STTAL, 2021)
The global share of Chinese container shipments grew from 10% in 2003 to 14% in 2019. Meanwhile, the share of dry bulk commodity imports to world volume has jumped sharply from only 11% to 34% in the same period. Based on the total dry bulk commodity, China's share in the global market is very dominant and is the main player in this industry. The rapid spread of the coronavirus has had a major impact on the global shipping market, with falling demand for goods from China impacting everything from container ships to oil tankers. Freight rates for global container lines generally fall sharply by between 10% -15%. The radical drop in demand for Chinese crude oil tankers from an average of 3.4 billion tonnes of miles per day in 2019 to almost zero. This is just the beginning of what will become a global crisis for all sectors including shipping. Therefore, this study aims to analyze the impact of the Coronavirus COVID-19 on the maritime industry, especially in Indonesia, as well as how to deal with the Coronavirus outbreak based on the recommendations of the World Health Organization (WHO) and the International Maritime Organization (IMO). The research method used in this research is a literature study with a descriptive analysis approach using the Content Analysis method as well as how to deal with the Coronavirus outbreak based on the recommendations of the World Health Organization (WHO) and the International Maritime Organization (IMO). The research method used in this research is a literature study with a descriptive analysis approach using the Content Analysis method as well as how to deal with the Coronavirus outbreak based on the recommendations of the World Health Organization (WHO) and the International Maritime Organization (IMO). The research method used in this research is a literature study with a descriptive analysis approach using the Content Analysis Method. Keywords: COVID-19, Maritime Industry, Global Shipping Market, Global Crisis, WHO and IMO